PENGEMBANGAN BAHAN AJAR TEMATIK TEMA PAHLAWANKU DENGAN PENDEKATAN KONTEKSTUAL DI KELAS IV SD - Putri Ayuni (JURNAL PENDIDIKAN DAN PEMBELAJARAN TERPADU (JPPT), 2022)
This development research aims to develop thematic teaching materials for the theme of my 5 heroes with a contextual approach that is appropriate for use in the learning process in grade IV. This research is a type of research and development using the ADDIE development model. In this study, researchers carried out the ADDIE development model only up to the development stage. The instrument used to collect data is a questionnaire or questionnaire given to several expert validators, namely material expert validators, language expert validators and learning expert validators. Based on the validation results from the material expert validator, a score of 80 was obtained with the "Eligible" criteria. From the results of the validation of linguists, a score of 80 was obtained with the "Eligible" criteria. From the results of the validation of learning experts, a score of 94.6 was obtained with the criteria of "Very Eligible". The average score from the assessment results of the three expert validators obtained a score of 84.86. According to the criteria for the assessment score, it can be said that the thematic teaching materials for the theme 5 heroes with a contextual approach developed are "appropriate" to be used in the learning process.